2003
DOI: 10.1002/humu.10195
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity within the R408W phenylketonuria mutation lineages in Europe

Abstract: For the PKU Special IssueThe R408W phenylketonuria mutation in Europe has arisen by recurrent mutation in the human phenylalanine hydroxylase (PAH) locus and is associated with two major PAH haplotypes. R408W-2.3 exhibits a west-to-east cline of relative frequency reaching its maximum in the Balto-Slavic region, while R408W-1.8 exhibits an east-to-west cline peaking in Connacht, the most westerly province of Ireland. Spatial autocorrelation analysis has demonstrated that the R408W-2.3 cline, like that of R408W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Several PAH mutations, identical by state in their nucleotide change, occur on two or more different haplotype backgrounds. For example R408W, the most prevalent pathogenic PAH allele, occurs prominently on haplotypes 1 and 2 in European-derived populations [John et al, 1990;Treacy et al, 1993;Eisensmith et al, 1995;Tighe et al, 2003]. Because a CpG dinucleotide is involved, R408W has the potential to be a recurrent mutation and identical only by state on haplotypes 1 and 2 [Byck et al, 1994;Tighe et al, 2003].…”
Section: Population Associationsmentioning
confidence: 99%
“…Several PAH mutations, identical by state in their nucleotide change, occur on two or more different haplotype backgrounds. For example R408W, the most prevalent pathogenic PAH allele, occurs prominently on haplotypes 1 and 2 in European-derived populations [John et al, 1990;Treacy et al, 1993;Eisensmith et al, 1995;Tighe et al, 2003]. Because a CpG dinucleotide is involved, R408W has the potential to be a recurrent mutation and identical only by state on haplotypes 1 and 2 [Byck et al, 1994;Tighe et al, 2003].…”
Section: Population Associationsmentioning
confidence: 99%
“…In the latter study, 18 Slavic compared with Italian subjects also had higher LVMI. Other investigators reported ethnic diversity between western European and Slavic populations in various genetic polymorphisms, [19][20][21] which is probably due to differing genetic evolution along the migration patterns when Europe started to be populated from the Middle East and North Africa. [22][23][24] Research into the SAH gene found its roots in studies of genes, which are overexpressed in genetically hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…Control DNA samples (n ¼ 60) from individuals of Irish ethnicity were obtained with informed consent and local ethical approval; these were used to analyse the extent of polymorphism of candidate SNP and STR markers. In addition, a set of anonymized singleton DNA samples from 15 European populations (n ¼ 117) was used to assess the level of wild-type GALT haplotype diversity; these were obtained previously in the context of a study of PAH gene VNTR sequence diversity (Tighe et al, 2003) and included: Republic of Ireland (n ¼ 72), Northern Ireland (n ¼ 10), Scotland (n ¼ 8), Spain (n ¼ 5), Germany (n ¼ 7), Denmark (n ¼ 4) and Poland (n ¼ 11).…”
Section: Methodsmentioning
confidence: 99%